See inside energy - James, Alice; Allen, Peter (Usborne Publishing London, England, 2017)
We all need energy for our lives - and lots of it. Find out what energy is, how it affects our planet and the exciting new inventions scientists are creating to make energy in the future, in this fascinating introduction to an important topic. With over 65 flaps to lift and links to specially selected websites to find out more